Macrobenthos from unvegetated intertidal areas in the Caeté river estuary in Bragança, Pará - Rosa Filho, José Souto; Busma, Debora Vieira; Viana, Andréa Pontes; Gregório, Aderson Manoel; Oliveira, Diogo Marques (Boletim do Museu Paraense Emílio Goeldi - Ciências Naturais, 2006)
The macrobenthic community structure was studied in inter-tidal, non-vegetated areas of the Caeté river estuary, Pará, Brazil, during the dry season of 2003. Four samples were collected at four stations on the downstream direction (P1 to P4) using a corer (0.008 m2 and 20 cm long). Samples were sieved through a 0,3 mm mesh and the organisms preserved in a 5% formaline saline solution stained with Bengal rose. At each station, sediment samples were collected and salinity and water temperature recorded. A total of 105,500 individuals were collected, divided in 17 taxa comprising the fphyla: Nemertea, Arthropoda and Annelida. Polychaeta dominated the assemblages (11 taxa and 87.25% of the individuals). The most abundant taxa were Mediomastus californienses, Nephtys fluviatilis and Oligochaeta (Tubificidae). Density and richness values varied from 2625 ind.m-2 and 3 taxa at station P1 to 96625 ind.m-2 among 16 taxa at station P4. Cluster analysis seperated three groups (50% similarity): Group 1, including samples from stations P3 and P4, was characterized by a relatively high salinity (22.6 to 26.5) and a fine sand substrate. This group, dominated by Sigambra grubii, was the richest (13 taxa), most diverse (χH´= 1.18) and abundant (χ= 12220 ind.m-2); Group 2, including samples from station P1, was characterized by a salinity of 5,1 and a silt-sandy substrate. This group presented the lowest richness (3 taxa), diversity (χH´= 0.67) and abundance (χ= 665 ind.m-2) values, and was dominated by the species Namalicastys abiuma; and Group 3, including samples from station P2, was characterized by a salinity of 3.6 and a silt-sandy substrate. N. abiuma was the most abundant species of this group that was characterized by intermediate richness (5 taxa), abundance (χ= 2010 ind.m-2) and diversity (χH´= 0.71) values. Thus, it is concluded that in the intertidal area of the non-vegetated Caeté river the species number is low; Annelida is the most abundant group; the species composition reflects.